MENJADIKAN YESUS SEBAGAI TELADAN DALAM PEMBENTUKAN KARAKTER ANAK ATAS DASAR KEHIDUPAN KELUARGA KRISTEN - Alfrida Ponno; Mariam Liku; Mejanti Patimang (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
This article is about the role of Christians in making Jesus an example in familiy life, one of the roles of the family is to carry out the basic principles of a believe’s life, namely faith, hope and love. The method used is a qualitative method which provides an explanation using analysis and tends to focus more on the theoretical basis. Jesus is the Savior, the Great teacher and should be used as a guide in family life and Jesus was willing to sacrifice His life to atone for human sins, He did all of that because of His love for us. Family consists of father, mother, children, in family life parents are responsible for educating children to the right path according to God’s word. In the family it is necessary to provide maximum character formation for children so that children grow up to be good and responsible children. In the family, parents are examples for children, for that parents must follow the example that Jesus taught, such as being humble, helpful, praying, not being selfish, being willing to forgive, being patient, and living in love with one another with true faith in Jesus. Children imitate and do it according to the will of Jesus and parents and children should discipline themselves to read the Bible every day.